2009
DOI: 10.1021/bm900512h
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nonpolar and Polar Intermolecular Interactions in the Improvement of the Drug Loading Capacity of PEO-b-PCL with Increasing PCL Content for Two Hydrophobic Cucurbitacin Drugs

Abstract: Molecular dynamics (MD) simulation was used to study the roles of nonpolar and polar intermolecular interactions in the improvement of the drug loading capacity of poly(ethylene oxide)-b-poly(epsilon-caprolactone) (PEO-b-PCL) with increasing PCL content for two water insoluble anticancer drugs: Cucurbitacin B (CuB) and Cucurbitacin I (CuI). In particular, random binary mixture models containing 10-12 wt % drug and remaining PEO-b-PCL with three different PCL/PEO (w/w) ratios (0.5, 1, and 2) were used to calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…This can be attributed to non-polar interactions between AmB and stearyl groups of the nanocarriers [23] and/or polar interactions between AmB and unconjugated COOH groups or extra carbonyl groups in MePEO-b-PStCL (in comparison to MePEO-b-PCL). [33,34] Nonetheless, the presence of free carboxyl groups on PCL block seemed to positively impact AmB solubilization, as block copolymers with >90% stearyl substitution showed reduced AmB solubilization (data not shown). In general, the extent of AmB solubilization achieved by MePEO-b-PCL, MePEO-b-PCCL, and MePEO-bPStCL nanocarriers at a polymer concentration of 2.5 mgÁmL À1 under current study, appears to be higher than AmB water solubility levels achieved by previously reported polymeric nanocarriers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This can be attributed to non-polar interactions between AmB and stearyl groups of the nanocarriers [23] and/or polar interactions between AmB and unconjugated COOH groups or extra carbonyl groups in MePEO-b-PStCL (in comparison to MePEO-b-PCL). [33,34] Nonetheless, the presence of free carboxyl groups on PCL block seemed to positively impact AmB solubilization, as block copolymers with >90% stearyl substitution showed reduced AmB solubilization (data not shown). In general, the extent of AmB solubilization achieved by MePEO-b-PCL, MePEO-b-PCCL, and MePEO-bPStCL nanocarriers at a polymer concentration of 2.5 mgÁmL À1 under current study, appears to be higher than AmB water solubility levels achieved by previously reported polymeric nanocarriers.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, both polar and non-polar interactions with the polymer are expected to affect the extent of AmB solubilization as well as release from its polymeric carrier. [33] On the other hand, MePEO-b-PStCL copolymer showed higher encapsulation efficiency compared to MePEO-b-PCL, despite a shorter PCL backbone. This can be attributed to non-polar interactions between AmB and stearyl groups of the nanocarriers [23] and/or polar interactions between AmB and unconjugated COOH groups or extra carbonyl groups in MePEO-b-PStCL (in comparison to MePEO-b-PCL).…”
Section: Discussionmentioning
confidence: 96%
“…al. had investigated the roles of nonpolar and polar intermolecular interactions in the improvement of the hydrophobic drug loading capacity of PEG-PCL with increasing PCL content (24).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing PCL/PEO ratio, both drugs showed an increase in solubility. This was attributed to the increase in favorable polar interactions and to the formation of additional hydrogen bonds between drugs and PCL rather than to the increase in hydrophobic characteristics (Patel et al, 2009). In their subsequent study, PCL was branched and linked to PEO as PEO-b-3PCL and tested for various drug encapsulations.…”
Section: Amphiphilic Copolymersmentioning
confidence: 99%